Role of organizational justice in linking leadership styles and academics' performance in higher education - Irfan Ullah Khan; Gerald Goh Guan Gan; Mohammad Tariqul Islam Khan; Naveed Saif (Administrative Sciences, 2023)
Leadership is vital for all organizations, including higher education institutions (HEIs). Based on this, this study aimed to examine department heads' leadership styles concerning employee performance as well as nurturing the culture of justice. For this purpose, the leadership styles (transformational and transactional leadership) relationship is examined with employee performance through the mediating role of organizational justice. Data were collected from academicians working in the HEIs located in the province of Khyber Pakhtunkhwa, Pakistan using a convenience sampling approach to obtain the targeted sample. Data were analyzed through a symmetric approach and after conducting confirmatory factor analysis (CFA) using AMOS, mediation models were assessed by following the Hayes process model procedure. The results indicate that organizational justice partially mediates the direct relationship between transformational and transactional leadership with employee performance in the HEIs sector of Pakistan. It is recommended that institutions need to take action to ensure that just and fair transformational leadership behavior is practiced to attain the desired employee performance in the HEIs.
Keywords: 350; employees' performance; higher education institutions; leadership styles; organizational justice